Analysis of protein profiles and peptides during in vitro gastrointestinal digestion of four Chinese dry-cured hams. (February 2020) - Jiang, Shui; Xia, Dong; Zhang, Danni; Chen, Gaole; Liu, Yuan
Abstract: In this study, the in vitro digestion with pepsin and trypsin enzymes was applied to mimic the gastrointestinal digestion of dry-cured hams from different producing districts of China. The analysis of digestibility and particle size revealed that the digestion characteristics of different dry-cured hams were significantly different ( p  < 0.05). During the gel electrophoresis analysis, protein profiles were characterized by analyzing 14 and 9 proteins generated during pepsin and pepsin/trypsin digestion. The relative intensities of protein bands could be used to distinguish different dry-cured hams based on principal component analysis (PCA) and linear discriminant analysis (LDA). According to the analysis of peptide profiles, more than 50% of peptides were distributed in the molecular weight ranging from 1500 to 2500 Da, and two-step digestion had little effect on peptide generation due to the cleavage site specificity of pepsin and trypsin. This study provided evidences that it was possible to identify producing districts of different dry-cured hams based on digested characteristics. Graphical abstract: Image 1 Highlights: Using in vitro digestion of four types dry-cured hams with pepsin and trypsin. PCA and LDA can distinguish different dry-cured hams based on protein profiles. Digestibility and particle size of different hams are significantly different. Peptides of in vitro digestion products are distributed in ranges of 1500–2500 Da. Two-step digestion with pepsin and trypsin had little effect on peptide generation.